Description of three new species of Pentelicus Howard (Hymenoptera: Encyrtidae) from India, with a key to world species - Manickavasagam, S.; Chaitanya, T. Krishna (Zootaxa, 2015)
Three new species of Pentelicus Howard (Hymenoptera: Encyrtidae) are described from Tamil Nadu, India: P. funiculatus sp. nov., P. punctatus sp. nov. and P. depunctatus sp. nov. A revised key to the world species of Pentelicus is also provided.